2007
DOI: 10.1002/jccs.200700071
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from the Leaves of Litsea Acutivena

Abstract: Continuous investigation of the CHCl3‐soluble and n‐hexane fractions of the leaves of Litsea acutivena Hayata (Lauraceae) led to the isolation of one new butanolide, acutilactone (1), one new lactone, 4‐nonacosyl‐dihydrofuran‐2‐one (2), together with 15 known compounds. The known compounds included one butanolide, one norisoprenoid, one quinone, two steroids, one triterpenoid, one coumarin, two fatty acids, one amide, and five other compounds. The structures of these compounds were determined by means of spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Investigation of the leaves of L. acutivena Hayata [ Actinodaphne acutivena (Hay.) Nakai] has led to the isolation of eight new compounds, the norneolignan dehydroxymethylailanthoidol ( 163 ); the butanolides, litseakolides D–G ( 164 – 167 ), isolincomolide D ( 168 ) [ 102 ], and acutilactone ( 169 ); and the lactone, 4-nonacosyl-dihydrofuran-2-one ( 170 ) [ 103 ].…”
Section: Phytochemical Studies Of Formosan Lauraceous Plantsmentioning
confidence: 99%
“…Investigation of the leaves of L. acutivena Hayata [ Actinodaphne acutivena (Hay.) Nakai] has led to the isolation of eight new compounds, the norneolignan dehydroxymethylailanthoidol ( 163 ); the butanolides, litseakolides D–G ( 164 – 167 ), isolincomolide D ( 168 ) [ 102 ], and acutilactone ( 169 ); and the lactone, 4-nonacosyl-dihydrofuran-2-one ( 170 ) [ 103 ].…”
Section: Phytochemical Studies Of Formosan Lauraceous Plantsmentioning
confidence: 99%
“…Assignment of signals was facilitated by COSY, HSQC and HMBC experiments. The known compounds obtained in this study, phytol acetate (1) (Itoh et al, 2003), triacontanol (2), (Tsai et al, 2007), phytol (3) (Itoh et al, 2003), and alpha kosin (5) (Woldemariam et al, 1992) were identified by comparison of their physical and spectroscopic data with literature reports.…”
Section: Identification Of Isolated Compoundsmentioning
confidence: 99%
“…In previous studies, the stems were found to contain a novel cyclopentenone, 5-dodecanyl-4-hydroxy-4-methyl-2cyclopentenone [2], glycerols, flavanols, lactones and acyclic monoterpene diols [1,3]. As part of our continuing investigation of Formosan Lauraceous plants, a new lignan, (+)-diasesamin (1), together with eight known compounds, (+)-sesamin (2) [4], (+)-episesamin (3) [5], stearic acid (4) [6], palmitic acid (5) [7], a mixture of β-sitosterol (6) and stigmasterol (7) [8], and a mixture of β-sitosterol-Dglucoside (8) and stigmasterol-D-glucoside (9) [9] were isolated from the stem extracts of this plant. Compounds 3-9 were reported for the first time from this species.…”
mentioning
confidence: 99%